2022
DOI: 10.3390/molecules27093011
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intracellular Iron in Switching Apoptosis to Ferroptosis to Target Therapy-Resistant Cancer Stem Cells

Abstract: Iron is a crucial element required for the proper functioning of the body. For instance, hemoglobin is the vital component in the blood that delivers oxygen to various parts of the body. The heme protein present in hemoglobin comprises iron in the form of a ferrous state which regulates oxygen delivery. Excess iron in the body is stored as ferritin and would be utilized under iron-deficient conditions. Surprisingly, cancer cells as well as cancer stem cells have elevated ferritin levels suggesting that iron pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 86 publications
2
17
0
Order By: Relevance
“…Phosphorylation of the FOXO3a by ERK triggers its degradation and thereby prevents cell cycle arrest by inducing apoptosis by triggering Bim and FasL activation. It is required for proper regulation of the cell cycle via inducing p27kip1 and cyclin D [ 48 ]. As a result, ERK-mediated FOXO3a degradation could enhance cellular survival and proliferation via cell cycle dysregulation.…”
Section: Clinical and Epidemiologic Studies Of Breast Cancer Incidenc...mentioning
confidence: 99%
“…Phosphorylation of the FOXO3a by ERK triggers its degradation and thereby prevents cell cycle arrest by inducing apoptosis by triggering Bim and FasL activation. It is required for proper regulation of the cell cycle via inducing p27kip1 and cyclin D [ 48 ]. As a result, ERK-mediated FOXO3a degradation could enhance cellular survival and proliferation via cell cycle dysregulation.…”
Section: Clinical and Epidemiologic Studies Of Breast Cancer Incidenc...mentioning
confidence: 99%
“…Studies on the cytotoxicity of CTX have mainly focused on apoptosis [ 7 , 25 ]. However, many studies have found that ferroptosis and apoptosis are closely linked, that apoptosis can be converted into ferroptosis under certain conditions, and that ferroptosis promotes cell sensitivity to apoptosis [ 26 , 27 ]. Hu et al found that apoptosis, pyroptosis, and ferroptosis together induced an immunosuppressive hepatocellular carcinoma microenvironment and γδ T-cell imbalance [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The major cause of skin ovary cancer is still understudy because most of studies are going on this issue to calculate the exact reason of developing these tumors. They are also still confused about the main reason of ovary cancer because not much points are getting related with the cancer stem cells [12]. By using different phenotype effects, they also take some cells from ovary to study the level of cancer cells present.…”
Section: Discussionmentioning
confidence: 99%